Современный словарь иностранных слов - Захаренко Е.Н. (Русский язык, 2000)
Экземпляры: ф.14 (20180116) / Инвентарный номер: 32851 / Цена: 111.56 / Сис.шифр: 81.2 Рус-4 / Авт.знак: С48 / ГРНТИ: 16 / ББК: 81.2 Рус-4